2017
DOI: 10.1016/j.psep.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Predicting concentrations of fine particles in enclosed vessels using a camera based system and CFD simulations

Abstract: -Trinanes, P. (2017). Predicting concentrations of fine particles in enclosed vessels using a camera based system and CFD simulations. Process Safety and Environmental Protection, Predicting concentrations of fine particles in enclosed vessels using a camera based system and CFD simulations AbstractOne of the main challenges in industries handling biomass is the consequence of the particle breakage of pelletised biomass in smaller fractions which can lead to fine particles smaller 500 ¿m that can form dust clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…According to [117], the explosive mixture of wood dust from biomass is at a concentration in the range of 100 g/m 3 to several kg/m 3 . In the cited work from 2015 [116], up to 50% more dust than the minimum explosive limit was detected. There is thus a risk of explosion when filling a large-capacity silo.…”
Section: Risks In the Process Of Storing Biomass For Energy Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [117], the explosive mixture of wood dust from biomass is at a concentration in the range of 100 g/m 3 to several kg/m 3 . In the cited work from 2015 [116], up to 50% more dust than the minimum explosive limit was detected. There is thus a risk of explosion when filling a large-capacity silo.…”
Section: Risks In the Process Of Storing Biomass For Energy Purposesmentioning
confidence: 99%
“…According to the World Health Organization (WHO), from 2021, healthy air is considered to be where the daily average concentration of PM2.5 particles does not exceed 15 µg•m −3 [115]. In the paper [116], the authors evaluated the danger of the dust component during the storage of biomass in large-capacity silos (50,000 m 3 and more). They found that in this type of biomass storage, dust particles together with fungal spores can create a dusty mixture that can be dangerous to the health of operators working with this biomass and can even form a highly flammable and explosive mixture in case of contact with a source of heat or fire.…”
Section: Risks In the Process Of Storing Biomass For Energy Purposesmentioning
confidence: 99%
“…For this investigation a mesh cell size of 9 mm was used; this was found to give an independent mesh as outlined in work conducted by Lulbadda Waduge et al [15] for the same domain and silo. In addition to the previous study, the traditional methods of CFD analysis needed be adjusted.…”
Section: Challenges Of Comparing Simulations To Experimentsmentioning
confidence: 99%
“…Je nachdem in welcher Umgebung der Staubfreisetzungsprozess stattfindet, wirken sich die Emissionen auch gesundheitsgefährdend für den Menschen aus, wobei das Risiko in Zusammenhang mit der Konzentration des freigesetzten Staubs, der Expositionsdauer und der Zusammensetzung des Materials steht. Aus diesen Gründen wird in vielfältiger Hinsicht an einer Möglichkeit gearbeitet, das Aufkommen von Partikelemissionen für einen Prozessschritt in Abhängigkeit von Material-und Prozesseigenschaften bei mechanischen Bearbeitungsverfahren von diversen Schüttgütern vorherzusagen [1][2][3][4][5][6][7][8].…”
Section: Einfü Hrungunclassified